The inhibitory effect of BKCa channels induced by autoantibodies against angiotensin II type 1 receptor is independent of AT1R. (25th April 2018) - Wang, Peng; Zhang, Suli; Ren, Jie; Yan, Li; Bai, Lina; Wang, Li; Wang, Pengli; Bian, Jingwei; Yin, Xiaochen; Liu, Huirong
Abstract: Autoantibodies against angiotensin II Type 1 receptor (AT1-AA) are routinely detected in the serum of preeclampsia patients, which results in an increase in vascular tone and an elevation in intracellular calcium concentration of rat vascular smooth muscle (VSM). The big conductance calcium-activated potassium channels (BKCa channels) account for the dominant outward currents in VSMCs, contributing to membrane hyperpolarization and vasodilation. In the present study, we investigated the effect of AT1-AA on BKCa channels. A preeclampsia model was established by passively immunizing healthy pregnant BALB/c mice with AT1-AA extracted from hybridoma culture supernatant. Blood pressure, serum AT1-AA levels, and urinary protein were measured in the immunized mice. BKCa channel expression was detected using qRT-PCR and immunohistochemical technique. The patch-clamp technique was used to record the single currents of BKCa channels in the HEK293T cells that had been transfected. AT1-AA immunized mice exhibited elevated AT1-AA and urinary protein levels compared with mice of the vehicle group. Systolic blood pressure was also increased in the immunized group. BKCa channel β1 -subunit expression was reduced in the mesenteric arteries of immunized mice. AT1-AA could inhibit the BKCa currents and the inhibitory effects were not completely reversed following the application of valsartan, an inhibitor of AT1 receptor. In conclusion, AT1-AA could decrease BKCa expression and inhibit BKCa activity independent of AT1R. These inhibitory effects are likely to be contributory factors in the promotion of increased vascular tone caused by AT1-AA in preeclampsia.